2021
DOI: 10.3390/nano11040850
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Beclomethasone in Liposomes and Hyalurosomes Improved with Mucin as Effective Approach to Counteract the Oxidative Stress Generated by Cigarette Smoke Extract

Abstract: In this work beclomethasone dipropionate was loaded into liposomes and hyalurosomes modified with mucin to improve the ability of the payload to counteract the oxidative stress and involved damages caused by cigarette smoke in the airway. The vesicles were prepared by dispersing all components in the appropriate vehicle and sonicating them, thus avoiding the use of organic solvents. Unilamellar and bilamellar vesicles small in size (~117 nm), homogeneously dispersed (polydispersity index lower than 0.22) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…As can be seen in Table 4 , the aerodynamic diameter of all nanosystems was ≤3 μm, without significant differences between the micellar systems and the drug dispersions, suggesting that during the nebulization process, the device was capable of forming small droplets with the appropriate size for pulmonary administration. Indeed, as previously reported, the devices mainly used for pulmonary administration may generate particles with different aerodynamic diameters, but only the smaller ones (MMAD between 1 and 5 μm) are deposited by gravitational settling in the deeper part of the lungs, while those with MMAD > 5 μm are generally recovered in the upper airways (mouth, trachea and main bronchi) by inertial impaction [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in Table 4 , the aerodynamic diameter of all nanosystems was ≤3 μm, without significant differences between the micellar systems and the drug dispersions, suggesting that during the nebulization process, the device was capable of forming small droplets with the appropriate size for pulmonary administration. Indeed, as previously reported, the devices mainly used for pulmonary administration may generate particles with different aerodynamic diameters, but only the smaller ones (MMAD between 1 and 5 μm) are deposited by gravitational settling in the deeper part of the lungs, while those with MMAD > 5 μm are generally recovered in the upper airways (mouth, trachea and main bronchi) by inertial impaction [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aerodynamic diameter (MMAD) and geometric standard deviation (GSD) values were calculated excluding the amount of drugs deposited in the induction port and were both extrapolated from the graph obtained by plotting the cumulative amount of particles with a diameter lower than the stated size of each stage as a percentage of each recovered drug versus the cut-off diameter, according to the European Pharmacopeia [ 25 , 26 ]. The total mass output (TMO%), the Fine Particle Dose (FPD), and the Fine Particle Fraction (FPF), which represent the percentage of drug recovered in the NGI versus the amount initially placed in the nebulizer, the amount of drug contained in droplets of size less than 5 μm, and the percentage of droplets with size less than 5 μm, respectively, were measured as previously reported [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the dyes are non-fluorescent when reduced, but become highly fluorescent upon oxidation. The most widely used dye is the 2 ,7 -dichlorofluorescin diacetate (DCFDA) that become oxidized into 2 ,7 -dichlorofluorescein (DCF) by intracellular ROS [11,14,22,26,28,29,32,33,35,42,45,50,68,72,[83][84][85][87][88][89]104]. Other commercially available fluorogenic probes are also available [13,24,69,80].…”
Section: Methods For Detecting Oxidative Stressmentioning
confidence: 99%
“…Besides affecting apoptosis and promoting cell senescence, it has been reported that CSE promotes other inflammatory forms of cell death, such as the pyroptosis or other forms of caspase-dependent cell deaths [12,14,15,27,28,[30][31][32][33][34]68,69,72,73,105]. Pyroptosis is a type of pro-inflammatory cell death promoted by caspase-1 activation and characterized by cell lysis and interleukin IL-1β release.…”
Section: Impact Of Cse On Senescence and Cell Deathmentioning
confidence: 99%
“…In particular, deformable vesicles, so called transfersomes, have been specifically designed for skin delivery and have sometimes been stabilized by adding hydrophilic polymers to the formulation. The latter interact with the bilayer in the internal and/or external surface, favoring sterically stabilized vesicles in dispersion [14][15][16]. Hydrophobically modified hydroxyethyl cellulose was previously used to coat liposomes, improving their stability [17].…”
Section: Introductionmentioning
confidence: 99%